Particulars, perspectives and time - Zhu, Z (2024)
Recent debates about mind and action have witnessed a growing interest in the ontology of the progressive aspect. This thesis puts this issue in a broader philosophical context by relating it to a series of inter-related questions concerning the ontology and semantics of events, the debate between three-dimensionalism and four-dimensionalism, the metaphysics of tense, and the nature of action and memory. This discussion develops an account of the progressive aspect as expressing an internal perspective on events and illustrates how this account can be integrated into a cohesive understanding of temporal perspectives, temporal particulars and reality.